Dignity-Contributing Factors In Clinical Care Settings: A Multisite Qualitative Descriptive Study - Asmaningrum, Nurfika; Huriah, Luluk; Tsai, Yun Fang (Jurnal Keperawatan Soedirman, 2020)
Background. The illness treated in hospital care environment increases the risk for loss of patient’s dignity. Hence, simultaneously preventing risk of losing dignity and maintaining patient dignity is important. Nevertheless, maintaining patient dignity depends on the knowledge of the factors influencing it. The present study aimed to explore the factors associated to dignified care in clinical care settings.Method. The study design was a multisite qualitative descriptive. This study was a multisite study conducted in six general hospitals located in East Java, Indonesia. The participants involved were 40 clinical nurses recruited from 36 medical and surgical wards. Data were analyzed using inductive content analysis.Results. Three main overarching categories contributing dignity care: nurse related factors involving commitment, competency and self-control; patient related factors involving personal traits and perception of care; and organization related factors involving staffing level and tangible resources.Conclusion. The study adds the understanding of factors contributing dignity gathered from healthcare provider viewpoints. These factors could act either as dignity-promoting factor or dignity-threatening factor. Our findings expanded the operationalization of the three areas as potential elements which could act as means to enhance dignity in care.